Psychosocial and Economic Burden of Cancer Disease in Sarawak - Yap, Shee Ling (Universiti Malaysia Sarawak (UNIMAS), 2020)
Cancer, as a common chronic disease, is one of the leading causes of death today. The number of cancer incidence is increasing from year to year. Having to live their remaining lives with cancer, cancer survivors require long term follow up care as well as support in terms of prevention, intervention for consequences of cancer treatment and cancer related follow-up care. The impact of cancer treatment has greater effects to the psychosocial and financial burden of the patients as well as their family members, which may in turn, affect their quality of life. The primary objective of this study is to analyse the psychosocial and economic burden of cancer in Sarawak. Data collection was conducted in Department of Radiotherapy, Oncology and Palliative Care Unit, Sarawak General Hospital. The findings of this study revealed the estimated value of the cost of cancer care across different socioeconomic variables and disease profiles. The impact of disease not only influence the financial costs but also may result in productivity lost in term of absenteeism and presenteeism. It was also found that social well-being and physical well-being are the primary areas in the overall quality of life (QOL) impacted by cancers. It was also found that financial toxicity has the mediator effect on the relationship between unmet needs and QOL. Given the growing number of cancer cases, it is important for the policymakers or providers to develop strategic plan and care in addressing the issue in order to help to reduce the burden of disease of cancer survivors as well as their families. Besides that, care plan is needed to address the area of concern of cancer survivors in order to improve their quality of life.